Analysis of Risk Management Implementation on the Financial Performance of the Regional Development Bank of West Java and Banten (Bank BJB) - Maman Sulaeman; Sopiah Herawati; Gun Gun Gunawan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study examines the effect of risk management implementation on the financial performance of Bank BJB (PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk) during the period 2015–2024. The research aims to analyze how credit risk (Non-Performing Loan), liquidity risk (Loan to Deposit Ratio), and capital adequacy (Capital Adequacy Ratio) influence Return on Assets as a measure of financial performance. Employing a quantitative explanatory design, the study uses secondary data from Bank BJB’s annual reports, financial statements, and good corporate governance reports. Data analysis is performed through multiple linear regression with classical assumption tests to ensure model validity. The results indicate that Non-Performing Loan has a negative and significant effect on Return on Assets, while Loan to Deposit Ratio and Capital Adequacy Ratio have positive and significant effects. These findings confirm that effective risk management significantly contributes to profitability and financial stability. The novelty of this research lies in its integration of risk management variables within the context of regulatory evolution, digital transformation, and post-pandemic recovery in Regional Development Banks. The study contributes to both academic literature and practical policy by providing empirical evidence on how prudent risk management can enhance bank performance and resilience. Keywords: Risk Management; Financial Performance; Non-Performing Loan; Loan to Deposit Ratio; Capital Adequacy Ratio